The Damage : a novel - Wahrer, Caitlin (New York : Pamela Dorman Books / Viking, 2021)
"When a small-town family is pushed to the brink, how far will they go to protect one of their own? A propulsive, gets-under-your-skin read about what we will do in the name of love and blood Tony has always looked out for his younger brother, Nick. So when he's called to a hospital bed where Nick is lying battered and bruised after a violent attack, his protective instincts flare, and a white-hot rage begins to build. Nick didn't ask for any of this. One moment he was partying at college; the next, he was at the center of an investigation threatening to tear not only him, but his entire family, apart. The real trouble? He can't remember a thing about what happened at the bar that night. And now his attacker, out on bail, is disputing Nick's version of what happened. Tony's wife, Julia, always knew that her husband's younger brother would be a huge part of their lives. As a a small-town New England lawyer, she works with kids like Nick all the time. She is determined to use her professional connections and keen intellect to make the best possible case for Nick. When Detective Rice gets assigned to the case, Julia feels they're in good hands. Especially because she senses that Rice, too, understands how things can quickly get complicated. Very complicated. As Julia tries to help her brother-in-law, she sees Tony's desire for revenge growing by the day. She wants justice for Nick, too, but Tony's preoccupation iss Julia tries to help her brother-in-law, she sees Tony's desire for revenge growing by the day. She wants justice for Nick, too, but Tony's preoccupation is scaring her. And before long, she finds herself asking: does she really know what her husband is capable of? Or of what she herself is? Exploring elements of doubt, tragedy, suspense, and justice, The Damage is an all-consuming read that marks the explosive debut of an extraordinary new writer"--.
Keywords: Mystery fiction; Suspense fiction